Application of Polamatika Techniques to Improve Operations Multiplication Tiled Capability in Low Vision Students Class VII in SLB-A YAPTI Makassar - Triyanto Pristiwaluyo; Tri Wahyuni (Department of Special Education, 2017)
The ability of blind students of class VII in SLB-A YAPTI Makassar in operating the multiplication decker is still very low. To improve the ability of the tiled multiplication operation attempted by applying techniques used polamatika. This study uses a quantitative approach and use this type of experimental research methods. Experimental research design used is Single Subject Research ABA (A (Baseline 1) - B (Intervention) - A (Baseline 2)). Subjects examined in this study is one student with low vision, 7th level at SLB-A YAPTI Makassar. Data collection techniques in this research is through tests and observation. The data obtained were processed by descriptive quantitative. The results showed that the ability of the tiled multiplication operation on low vision students of class VII in SLB-A YAPTI Makassar after using the technique of polamatika on the number of tens of tiled multiplication operations with units, with dozens to tens able to achieve the target behavior, although the operations Stackable multiplying numbers with hundreds and hundreds to tens unit yet fully achieve the target behavior. Based on these results it can be concluded that an increase in the ability of the tiled multiplication operation on low vision students in SLB-A YAPTI Makassar after using the polamatika techniqueKemampuan siswa tunanetra kelas VII di SLB-A YAPTI Makassar dalam mengoperasikan perkalian bersusun masih sangat rendah. Untuk meningkatkan kemampuan operasi perkalian bersusun dicoba dengan menerapkan teknik polamatika. Penelitian ini menggunakan pendekatan kuantitatif dan jenis metode penelitian eksperimen. Desain penelitian eksperimen yang dipergunakan adalah Single Subject Research A-B-A (A (Baseline 1) - B (Intervensi) - A (Baseline 2)). Subyek penelitian adalah Subjek yang diteliti dalam penelitian ini adalah satu orang siswa tunanetra laki-laki jenis low vision, inisial HD, kelas VII di SLB-A YAPTI Makassar. Teknik pengumpulan data dalam penelitian ini adalah melalui tes dan observasi. Data yang diperoleh diolah secara deskriptif kuantitatif. Hasil penelitian menunjukan bahwa kemampuan operasi perkalian bersusun pada siswa low vision kelas VII di SLB-A YAPTI Makassar setelah menggunakan teknik polamatika pada operasi perkalian bersusun bilangan puluhan dengan satuan, dan puluhan dengan puluhan, dapat mencapai target behavior, meskipun pada operasi perkalian bersusun bilangan ratusan dengan satuan dan ratusan dengan puluhan belum dapat sepenuhnya mencapai target behaviour. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa terjadi peningkatan kemampuan operasi perkalian bersusun pada siswa low vision di SLB-A YAPTI Makassar setelah menggunakan teknik polamatika.